Educação escolar indígena: as práticas culturais indígenas na ação pedagógica da Escola Estadual Indígena São Miguel Iauaretê (AM) - Ferreira, Geraldo Veloso (2007)
This study is focused upon the North Region of Brazil, northwest of the State of Amazonas, town of São Gabriel da Cachoeira, district of Iauaretê, Indigenous State School São Miguel. This region has a barely exclusively indigenous population that claims to have a differentiated education practice. It investigates the missionary pedagogical action in the indigenous Iauaretê education process, regarding the new proposal of Indigenous School Education, seeking alternatives for the establishment of that educational model. It also approaches the study about the indigenous school education and the subjects that help to understand the indigenous cultures as a process of pedagogical action in the Indigenous State School São Miguel of Iauaretê. The main proposal is to debate about the adequate curriculum to be used by the institution of indigenous education, mainly in the context of education in the region of Iauaretê. This becomes essentially important for the indigenous of that region, as it contributes to their formation according to the needs of their reality. The subject of this study, The Indigenous Cultural Practices in the Pedagogical Action, in the Indigenous State School São Miguel Iauaretê (AM), considers the indigenous cultural practices as elements that express and fortify their identity, as well as a curriculum elaboration that attend properly to the singularity of the indigenous school education in São Miguel Iauaretê. The valorization of the language, of the historical memory and also of the "science" of each people will be increased by this educational proposal, although it does not mean a disconnection with the technical and scientific knowledge built during the centuries by non-indigenous. It is about the use of adequate educational stuff and resources originated from the indigenous culture for use in a strict indigenous education. The elements of the indigenous culture of São Miguel can and should be used as curricular contents validated by the local, regional and national community